KETELADANAN SOSIAL NABI SEBAGAI MODEL PEMBELAJARAN AKHLAK DI KURIKULUM MERDEKA - Muhammad Abrar (Yayasan An-Nur Meunara Baro, 2025)
The moral crisis among students poses a serious challenge to Indonesia’s education system, especially when Islamic education focuses more on cognitive content than on internalizing ethical values. The social exemplary conduct of Prophet Muhammad such as honesty, empathy, responsibility, and tolerance offers a contextual and applicable model for moral education within Islamic Religious Education (PAI). This study aims to examine the relevance of the Prophet’s social exemplary character as a pedagogical model within the Merdeka Curriculum. Employing a descriptive-qualitative approach through literature review, interviews with Islamic education teachers, and observations in junior high schools, this research finds that the integration of the Prophet’s social values aligns closely with the Pancasila Student Profile. Learning strategies based on the Prophet’s social example not only enhance students’ understanding of moral values but also foster reflective and empathetic attitudes in social life. Teachers applying this approach report increased student engagement in value-based discussions and character formation. The findings suggest that the Prophet’s example serves not only as subject matter but also as a transformative pedagogical method. This article contributes by offering a contextual moral education model that aligns with the character-building goals of the Merdeka Curriculum.